2021
DOI: 10.1038/s41598-021-01449-2
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory seizure forecasting with a wrist-worn device using long-short term memory deep learning

Abstract: The ability to forecast seizures minutes to hours in advance of an event has been verified using invasive EEG devices, but has not been previously demonstrated using noninvasive wearable devices over long durations in an ambulatory setting. In this study we developed a seizure forecasting system with a long short-term memory (LSTM) recurrent neural network (RNN) algorithm, using a noninvasive wrist-worn research-grade physiological sensor device, and tested the system in patients with epilepsy in the field, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…The assessment of seizure risk in epilepsy may be improved further by combining long timescale cycles based seizure risk characterization with an acute seizure forecast layer, which has shown early promise with multimodal wearable devices. 46 More work is needed to optimize the performance of multimodal wearable sensors, however, the results from our straightforward approach are encouraging. Even if multimodal wrist-worn devices are unable to attain the performance of a brain implant, the ease of implementation, lower cost, broad applicability, and patient preference for a wrist-worn form factor 49 make this a critical area of study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The assessment of seizure risk in epilepsy may be improved further by combining long timescale cycles based seizure risk characterization with an acute seizure forecast layer, which has shown early promise with multimodal wearable devices. 46 More work is needed to optimize the performance of multimodal wearable sensors, however, the results from our straightforward approach are encouraging. Even if multimodal wrist-worn devices are unable to attain the performance of a brain implant, the ease of implementation, lower cost, broad applicability, and patient preference for a wrist-worn form factor 49 make this a critical area of study.…”
Section: Discussionmentioning
confidence: 93%
“…The device’s on-board memory is cleared after each upload. As previously described 46 electrographic seizures were verified by a board certified epileptologist (N.M.G) and experienced reader (J.B.). Seizure analyses were limited to subjects for whom ‘long-episodes’ available for visual confirmation did not exceed the device’s storage capacity except rarely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizure is a chronic, recurring condition that can mostly be prevented through medication before onset [51], but even with the best medications, 30% of the patients are drug-resistant [52]. Closed-loop brain stimulation has been found to mitigate and even improve symptoms [53], [54], but unpredictability of seizure requires a closed-loop prediction system to provide accurate warning with adequate preparation time for stimulation [55]. This calls for the need for fast, low-latency computations, as the changes within the patients can be noticed early-on, in order to start treatments early to improve safety and quality of life [56].…”
Section: Recent Work By Liu Et Al Implemented Finite Impulsementioning
confidence: 99%
“…This can and should be accomplished by the following 7 interventions: brain and carotid imaging, neurology consultation, antihypertensive treatment, anticoagulants for atrial fibrillation, anti-thrombotic medication, and statins. A recent American study showed that only a third (34.3%) of patients actually received these interventions without fail after a TIA [3]. Epilepsy care is another example where quality-of-care measures are not sufficiently adhered to in clinical practice, as Prof. Clarke illustrated by means of some of the quality-of-care measures from the American Academy of Neurology (AAN):…”
Section: Getting Evidence Into Practicementioning
confidence: 99%